The leaf spot complex on highland bananas in Uganda - Tushemereirwe, Wilberforce K.; Karamura, E.B.; Holderness, M.; Gold, C.; Deadman, M.L. (International Society for Horticultural Science, 2000)
The effects of a leaf spot complex (including Mycosphaerella musicola, M. fijiensis and Cladosporium musae) and leaf pruning on plant growth and yield in highland bananas were investigated in a field trial at Kawanda Agricultural Research Institute. Results from the first ratoon crop revealed that the leaf spot complex depressed plant height (3%) and yield (37%) in the highland banana Mbwazirume as compared to fungicide (triadimenol) treated plants.